2011
DOI: 10.1371/journal.pone.0017014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Peripheral Blood Mononuclear Cells in Pancreatic Cancer Patients Identifies Novel Genes with Potential Diagnostic Utility

Abstract: BackgroundIt is well known that many malignancies, including pancreatic cancer (PC), possess the ability to evade the immune system by indirectly downregulating the mononuclear cell machinery necessary to launch an effective immune response. This knowledge, in conjunction with the fact that the trancriptome of peripheral blood mononuclear cells has been shown to be altered in the context of many diseases, including renal cell carcinoma, lead us to study if any such alteration in gene expression exists in PC as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 28 publications
2
104
1
1
Order By: Relevance
“…Furthermore, CD4þ T cells derived from miR-17-92 transgenic mice exhibit an enhanced type-1 phenotype associated with increased interferon-g production and very late antigen (VLA)-4 expression. Baine and colleagues (17) reported the first in-depth comparison between global gene expression profiles of PBMCs from pancreatic cancer patients and healthy controls. Those authors identified a gene predictor set that could potentially be further developed for use in diagnostic algorithms for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CD4þ T cells derived from miR-17-92 transgenic mice exhibit an enhanced type-1 phenotype associated with increased interferon-g production and very late antigen (VLA)-4 expression. Baine and colleagues (17) reported the first in-depth comparison between global gene expression profiles of PBMCs from pancreatic cancer patients and healthy controls. Those authors identified a gene predictor set that could potentially be further developed for use in diagnostic algorithms for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this idea, it would be useful to study the role of microRNAs in peripheral blood mononuclear cells (PBMCs) in the context of diagnosis and prognosis of malignant tumors. Several studies have identified transcripts expressed differentially between PBMCs from cancer patients and normal subjects, and some of these expression changes seem to reflect specific immune responses of circulating cells (16,17). However, few studies have been done on PBMC microRNAs, which could be of use as diagnostic biomarkers for pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…41 In our study, ADAMTS20 has increased just after insulin application, but after that, it has decreased in day 3 and protected its low level throughout the study interval. Baine et al 45 showed that ADAMTS20 could distinguish pancreatic cancer patients from healthy controls and ADAMTS20 may be potential diagnostic marker in pancreas cancers. In the present study, ADAMTS20 was found to be decreased gradually in chondrosarcoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Human Annexin A3 genes are dispersed throughout the genome on chromosomes 4 q13-q22, including the two main isoforms of 33 kD and 36 kD [20]. Many studies have shown that changes in Annexin A3 expression have an important impact on the onset, development, drug resistance, and metastasis of tumors [12][13][14][15][16][17][18]26]. The expression of Annexin A3 in carcinoma tissues is also closely associated with cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A3 may act as a tumor suppressor or tumor promoter depending upon the type of tumor cell and tissue. Annexin A3 has been shown to be upregulated [13] in prostate cancer, and downregulated in kidney and thyroid cancers [14,15]. Increased expression of Annexin A3 enhanced the drug resistance of ovarian and liver cancers [16,19], promoted the progression of pancreatic, rectal, and glandular cancers [17], and accelerated the metastasis of lung cancer [18].…”
mentioning
confidence: 99%